Study on Sensitivity Pattern of Acinetobacter spp. from Clinical and Environmental Samples of National Medical College, Birgunj, Nepal - Gupta, Ravi Shankar; Shidiki, Amrullah; Karn, Naval Kishor; Jha, Chandana; Panday, Parbhakar Raj (Med Phoenix, 2025)
Introduction: Acinetobacter spp. are saprophytic ubiquitous gram-negative coccobacilli can survive for long periods on dry or moist inanimate surfaces and as commensals on the skin of man and animal which can facilitate its persistence and spread in healthcare facilities. The aim of study is to isolate and evaluate Acinetobacter spp. from clinical and environmental samples for its antibiotic susceptibility profile. Materials and Methods: This cross-sectional study was conducted at National Medical College and Teaching Hospital (NMCTH), Birganj, Nepal. 500 samples were collected from patients and environment of NMCTH. The samples were processed by use of culture media viz. Chocolate agar (CHA), 5% Sheep Blood agar (BA), and MacConkey agar (MA) plates for isolation of Acinetobacter spp. The characterization of antimicrobial susceptibility profile of isolated Acinetobacter spp was studied by use of Modified Kirby-Bauer disc diffusion technique. Results: 39.86% Acinetobacter spp were obtained from 276 clinical specimens whereas 48.21% Acinetobacter spp. from 224 environmental samples. The distribution of Acinetobacter spp, more were found in respiratory samples (67.24%), which followed by invasive samples (25.71%) and urinary samples (18.18%). Regarding antibiotic resistance profile, 92.7% Acinetobacter spp showed resistance cefixime, followed by 89% to amoxicillin-clavulinic acid and 86.2% against cefotaxime. Conclusion: The finding of current study suggests the need of direct efforts to reduce hospital-acquired infections and recommend the revision of the treatment protocol for Acinetobacter infections.